The Effect of Green Marketing, Social Media Marketing, Word of Mouth And Service Quality on Purchasing Decisions - Dewi Murtiningsih; Robby Dharma; Yananto Mohadi Putra (Digital Innovation : International Journal of Management, 2024)
The formulation of the problem in this research is: Does green marketing influence purchasing decisions? Does social media marketing influence purchasing decisions? Does word of mouth influence purchasing decisions? Does service quality influence purchasing decisions? The objectives of this research are: to determine the influence of green marketing on purchasing decisions, to determine the influence of social media marketing on purchasing decisions, to determine the influence of word of mouth on purchasing decisions, to determine the influence of service quality on purchasing decisions. This research is included in exploratory research. The population in this study is unknown, the number of samples in this study was 220. The analysis tool uses PLS. The research results show that green marketing has no significant effect on purchasing decisions, social media marketing has a significant effect on purchasing decisions, word of mouth has a significant effect on purchasing decisions, and service quality has a significant effect on purchasing decisions.